The Oxford handbook of Seventh-day Adventism - Campbell, Michael W. (Oxford Handbooks, 2024)
Seventh-day Adventism is the largest religious group to have emerged out of the Millerite revivals of the 1840s. When Christ's literal return to earth did not materialize in 1844, Adventists searched for biblical explanations. They wove together beliefs in the heavenly sanctuary, the seventh-day Sabbath, and Christian mortalism into a cohesive theology. Along with their premillennial eschatology, these beliefs served as the foundation of a new denomination under the leadership of James and Ellen White and abolitionist reformer Joseph Bates.By the early twentieth century, the Adventist movement had spread around the globe, and had made cultural contributions to medical science, health foods, archaeology, and education. This Oxford Handbook contains 39 original essays addressing many aspects of Adventism. Broad and comprehensive in scope, each chapter addresses the history, theology, and social aspects of Adventism, and maps the development of its most influential manifestation. Authors from around the world, and from both inside and outside the Adventist tradition, have come together to produce this authoritative work on Adventism